Black women in nursing history: the cultural competence in Maria Barbosa Fernandes´ trajectory - Fernanda Batista Oliveira Santos; Ana Renata Moura Rabelo; Bruna Dias França; Fernanda Alves dos Santos Carregal; Rita de Cassia Marques; Kênia Lara da Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to know the professional trajectory of the black nurse Maria Barbosa Fernandes and to analyze elements of her professional practice based on the cultural competence model of CampinhaBacote. Methods: historical-social study with an analysis of the findings in light of the Cultural Competence model. Results: Maria Barbosa was the first black woman to earn a nursing degree at the Escola de Enfermagem Carlos Chagas (Carlos Chagas Nursing School) (1935-1938), and the documentation about her history allowed us to infer the experience of discrimination and invisibility. However, her professional trajectory was marked by careful attention to the singularities and the sociocultural reality of individuals, with an emphasis on acting in vulnerable scenarios. Final Considerations: the pairing of the theme of black women in nursing with the reference of Cultural Competence consists of an invitation to value diversity in the profession and seek to move towards care committed to overcoming inequalities, through inclusive practices and culturally sensitive care.